The Impact Of New Innovation Technologies On Improving Quality Of Nursing Care In Family Health Settings: A Systematic Review Of Recent Evidence (Journal of Namibian Studies : History Politics Culture, 2023)
Background: The delivery of patient care and clinical procedures has changed because of technology's incorporation into healthcare systems. Optimizing healthcare delivery requires a thorough understanding of the effects of innovation technologies on patient safety, nursing workflows, and healthcare outcomes.Aims: To provide a thorough analysis of how the introduction of technology has affected patient safety, nursing practices, and healthcare outcomes in healthcare settings. The study aims to clarify the complex impacts of innovation technologies on several aspects of healthcare delivery using a systematic review and meta-analysis.Method: This thesis employs a mixed-method approach to give a thorough knowledge of the influence of technology on healthcare delivery by synthesizing data from empirical research, systematic reviews, and literature reviews. The sample populations comprise a range of healthcare environments, such as critical care units, acute care centers, and assisted living facilities. Findings: The findings emphasize the complex effects of technology adoption in healthcare environments. Health technologies impacts on nursing workflows range depending on the system, even though it has shown promise in improving patient safety by lowering prescription mistakes and increasing adherence to practice recommendations. Furthermore, it appears that technology-based learning resources will help nurses learn more effectively, which will lead to better patient care.Conclusion: the integration of technology has the potential to significantly improve the delivery of healthcare services. This includes but is not limited to strengthening patient safety, optimizing nursing workflows, promoting evidence-based practices, and improving patient outcomes. However, in order to overcome obstacles and fully use the advantages of technology in healthcare settings, strong implementation techniques and ongoing education are essential.